Comparison of growth performance and non‐specific immunity of Nile tilapia ( Oreochromis niloticus ) fed with non‐germinated and germinated faba bean - Xi Xie; Meiyan Chen; Qingqing Li; Ling Yang; Zhendong Qin; Lijuan Zhao; Shaowen Liang; Li Lin (Journal of Fish Biology, 2025)
Faba bean ( Vicia faba L.) has garnered interest from the aquatic feed industry as a plant‐based ingredient that may enhance muscle hardness and crispness in tilapia. However, faba beans contain numerous anti‐nutritional factors (ANFs) that could affect animal growth and health through their metabolic products. Germination effectively reduces the content of ANFs in faba beans; however, the effects of germinated faba beans on tilapia growth and non‐specific immunity remain unclear. In this study, the growth parameters, antioxidant activity, carbon metabolic enzyme activity and immune‐related gene expression profiles of tilapia fed with germinated faba beans (FB1 and FB5 groups) and non‐germinated faba beans (FB0 group) were compared. The FB1 and FB5 groups exhibited heavier body weight (514.39 ± 111.66 g and 546.87 ± 98.16 g) compared to the FB0 group (392.53 ± 78.34 g) on day 80 ( p interleukin‐1 beta ( IL‐1β ), C‐C motif chemokine ligand 3 ( CCL3 ) and tumour necrosis factor‐alpha ( TNF‐α ) were downregulated initially and then gradually upregulated by day 80. Expression of heat shock protein 70 ( Hsp70 ) upregulated in the FB1 and FB5 groups relative to that in normal tilapia (control). These findings suggest that incorporating faba beans into tilapia feed may reduce oxidative stress and modulate immune responses in tilapia cultures.